2010
DOI: 10.1111/j.1365-2702.2010.03407.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the follow‐up care needs of patients treated for colorectal cancer

Abstract: Nurse-led clinics and/or telephone follow-up by specialist nurses may be effective models of care for this particular patient group, providing appropriate access for meeting clinical, psycho-social and information needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 39 publications
7
114
0
5
Order By: Relevance
“…[2023, 37] Benefits to nurse-led follow up included improved access to care, continuity, patient education and perceived support in coping with their disease. [21, 23] Four studies suggested willingness to engage the GP or FP in a larger role in follow-up[26, 27, 33, 40]. This was particularly favored among patients who endorsed a strong patient-physician relationship with their GPs[33], however, some patients expressed concern about losing contact with specialists [27].…”
Section: Resultsmentioning
confidence: 99%
“…[2023, 37] Benefits to nurse-led follow up included improved access to care, continuity, patient education and perceived support in coping with their disease. [21, 23] Four studies suggested willingness to engage the GP or FP in a larger role in follow-up[26, 27, 33, 40]. This was particularly favored among patients who endorsed a strong patient-physician relationship with their GPs[33], however, some patients expressed concern about losing contact with specialists [27].…”
Section: Resultsmentioning
confidence: 99%
“…This supports previous reports describing uncertainty throughout the illness journey and in relation to the future, families, treatment, coping mechanisms, worsening illness (Beaver et al., 2010; Browne et al., 2011; McCaughan et al., 2011; Shaha, Cox, Talman, & Kelly, 2008; Taylor et al., 2010). Feeling uncertain is common to the experience of many diseases (Etkind, Bristow, Bailey, Selman, & Murtagh, 2016; Kimbell, Boyd, Kendall, Iredale, & Murray, 2015; Taylor, Wells, Hubbard, & Worth, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies have helped to explore various aspects of individuals' experiences of colorectal cancer such as the psychosocial impact and quality of life (Dunn et al, 2005;Ramfelt et al, 2002;Sahay et al, 2001), adjustment to diagnosis and treatment (Hubbard et al, 2010;Taylor et al, 2001Taylor et al, , 2010 including an ostomy or stoma (McMullen et al, 2008(McMullen et al, , 2014, and healthcare needs or preferences (Beaver et al, 2010;McCaughan et al, 2011McCaughan et al, , 2012Rozmovits et al, 2004). Some studies have included partners or other relatives, describing issues such as their information needs (Broughton et al, 2004), the impact of treatment (Emslie et al, 2009;Ohlsson-Nevo et al, 2011, caregiving and daily life (Houldin, 2007;Sjovall et al, 2011), along with the economic and emotional consequences (Céilleachair et al, 2012).…”
Section: Introductionmentioning
confidence: 99%